Optimization of Distribution Routes by Way of the Multilevel Approach to the Traveling Salesman Problem - Jiri Cejka; Mykola Guchenko (Communications - Scientific letters of the University of Zilina, 2017)
The article „Optimization of Distribution Routes by way of the Multilevel Approach to the Traveling Salesman Problem“ is concerned with the optimization of the distribution routes. The goal is to use the obtained data to try to optimize and propose alternatives of the circular routes for the company Vltavotynske lahudky. For implementing this task, the principle of the module for solving the transport-related tasks was used. This module was developed by the Department of the Operational and System Analysis of the Czech University of Life Sciences in Prague.